Design Optimize of Cylindrical Gear Reducer Used in Axial Flow Fan of Direct Air Cooled System - Liu Haidong; Li Qin (Jixie chuandong)
For solving the frequent failure problem of the cylindrical gear reducer which used in axial flow fan in direct air cooled system. By using the KISSsoft software,the gear reducer is analyzed,and the dangerous points of this reducer is found. According to the analysis result,the structure improvement and checkout are conducted. The result shows that the structures after improvement satisfied the requirements of strength and rigidity. The reference for series of products design and further improvement of gear reducer is provided by the obtained analysis data.